The Effect of Medicare Accountable Care Organizations on Early and Late Payments for Cardiovascular Disease Episodes. Issue 8 (August 2018) - Sinha, Shashank S.; Moloci, Nicholas M.; Ryan, Andrew M.; Markovitz, Adam A.; Colla, Carrie H.; Lewis, Valerie A.; Hollenbeck, Brent K.; Nallamothu, Brahmajee K.; Hollingsworth, John M.
Abstract : Background: Initial evaluations of the Pioneer and Shared Savings Programs have shown modest savings associated with care receipt in a Medicare accountable care organization (ACO). Whether these savings are affected by disease chronicity and the mechanisms through which they occur are unclear. In this context, we examined the association between Medicare ACO implementation and episode spending for 2 different cardiovascular conditions. Methods and Results: We analyzed a 20% sample of national Medicare data, identifying fee-for-service beneficiaries aged ≥65 years admitted for acute myocardial infarction (AMI) or congestive heart failure (CHF) between January 2010 and October 2014. We distinguished admissions to hospitals participating in a Medicare ACO from those to hospitals that were not. We calculated 365-day, price-standardized episode spending made on behalf of these beneficiaries, differentiating between early (index admission to 90 days postdischarge) and late payments (91-365 days postdischarge). Using an interrupted time series design, we fit longitudinal multivariable models to estimate the association between hospital ACO participation and episode spending. Our study included 153 476 beneficiaries admitted for AMI to 401 ACO participating hospitals and 2597 nonparticipating hospitals and 260 420 beneficiaries admitted for CHF to 412 ACO participating hospitals and 2796 nonparticipating hospitals. On multivariable analysis, admission to an ACO participating hospital was not associated with changes in early episode spending (AMI, 95 per beneficiary; 95% CI, −481 to 671; CHF, 158; 95% CI, −290 to 605). However, it was associated with significant reductions in late episode spending for both cohorts (AMI, −680; 95% CI, −1348 to −11; CHF, −889; 95% CI, −1465 to −313). Conclusions: For beneficiaries with AMI or CHF, admission to ACO participating hospitals was not associated with changes in early episode spending, but it was associated with significant savings during the late episode. ACO effects on late episode spending may complement other value-based payment reforms that target the early episode. Abstract : Supplemental Digital Content is available in the text.